2020
DOI: 10.3389/fneur.2020.00238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mitophagy on Regulatory T Cell Function in Patients With Myasthenia Gravis

Abstract: This study was conducted to determine whether regulatory T cells (CD4 + CD25 + T, Tregs) show abnormal mitophagy as well as the function of Tregs in patients with myasthenia gravis (MG). Methods: CD4 + T cells and CD4 + CD25 + Treg cells were obtained from 15 patients with MG (MG group) and 15 controls (N group). Tregs from the MG group were subjected to rapamycin-induced culture for 48 h (Rapa group) and 3-methyladenine-induced culture for 48 h (3-MA group). The levels of mitophagy in Tregs were then observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Recent reports showed that the MT membrane potential and the proliferation inhibition function of CD4 + Foxp3 + Treg from patients with myasthenia gravis are enhanced by autophagy inducing agent rapamycin and suppressed by phosphoinositide 3-kinase (PI3 kinase) and autophagy inhibitor 3-methyladenine (3-MA) ( 102 ) and that during autoimmune conditions, Treg function alterations associate with MT oxidative stress, dysfunctional mitophagy, and enhanced DNA damage and cell death ( 103 , 104 ). We hypothesized that the expressions of OCRGs are modulated in CD4 + CD25 high FOXP3 + Treg in comparison with those of CD4 + CD25 − T effector cell controls.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports showed that the MT membrane potential and the proliferation inhibition function of CD4 + Foxp3 + Treg from patients with myasthenia gravis are enhanced by autophagy inducing agent rapamycin and suppressed by phosphoinositide 3-kinase (PI3 kinase) and autophagy inhibitor 3-methyladenine (3-MA) ( 102 ) and that during autoimmune conditions, Treg function alterations associate with MT oxidative stress, dysfunctional mitophagy, and enhanced DNA damage and cell death ( 103 , 104 ). We hypothesized that the expressions of OCRGs are modulated in CD4 + CD25 high FOXP3 + Treg in comparison with those of CD4 + CD25 − T effector cell controls.…”
Section: Resultsmentioning
confidence: 99%
“…Raised cerebrospinal fluid and plasma indicants of autophagy and mitophagy, including PINK1 and parkin, are evident in the active phase of relapse remitting multiple sclerosis, with autophagy inhibition enhancing myelination, highlighting that the enhancement, as well as the suppression, of mitophagy are aspects of 'autoimmune' disorders [53]. Dysregulated mitophagy is evident in many classical 'autoimmune' disorders, including rheumatoid arthritis [54], SLE [55], T1DM [56], myasthenia gravis [57] and autoimmune hepatitis [58], as well as in suspected 'autoimmune' conditions, such as endometriosis [59], and neurodegenerative conditions [60]. Notably, alterations in mitochondrial function and mitophagy are not always evident in cells classically associated with these conditions, but in cells relevant to wider intercellular interactions, including immune cell mitochondria, as evident in Treg in myasthenia gravis [57].…”
Section: Mitochondrial Metabolism and 'Autoimmunity'mentioning
confidence: 99%
“…Dysregulated mitophagy is evident in many classical 'autoimmune' disorders, including rheumatoid arthritis [54], SLE [55], T1DM [56], myasthenia gravis [57] and autoimmune hepatitis [58], as well as in suspected 'autoimmune' conditions, such as endometriosis [59], and neurodegenerative conditions [60]. Notably, alterations in mitochondrial function and mitophagy are not always evident in cells classically associated with these conditions, but in cells relevant to wider intercellular interactions, including immune cell mitochondria, as evident in Treg in myasthenia gravis [57]. Such data implicate a 'microenvironment' of diverse interacting cells with their mitochondrial function dynamically shaped via alterations in the mitochondrial function of other 'microenvironment' cells, paralleling the dynamic intercellular interactions occurring within the tumor microenvironment [61], and as recently proposed for T1DM [17].…”
Section: Mitochondrial Metabolism and 'Autoimmunity'mentioning
confidence: 99%
“…The use of immunosuppressive Tregs for therapeutic purposes is of great interest to researchers because of their great potential in the treatment of autoimmune diseases, prevention of transplant rejection, and tumor immunotherapy [7][8][9] . Previous research in our research group showed that the abnormal mitophagy in peripheral blood Treg cells in patients with myasthenia gravis (MG) [10] . In this research, the autophagy state of mitochondria was changed In Vitro by using different CCCP concentrations in Tregs.…”
Section: Introductionmentioning
confidence: 95%